The Education and Training of Public Servants
XVIII, 395 p.
Keywords: “This book makes at least two significant contributions to the literature. It enhances our knowledge of how civil servants are prepared for their service, and the opportunities they have to continue to enhance their skills. It also discusses the issue of education and training over a significant time period. The authors and editors are also to be commended for the detailed research, and the coherent presentation of a wealth of information.” — B. Guy Peters, University of Pittsburgh, USA “This superb new collection is a massive step forward in explaining how some societies have built effective strategies for training and supporting those charged with ensuring the widest possible benefit in the implementation of policy and why others are still distorted by privilege, dogma and powerful vested interests. It should be required reading for all those entering public service and for all those charged with recruiting, mentoring andcultivating the common good.” — Ian Cawood, Stirling University, UK This book examines systems and practices of public service education and training in an international context. Focusing especially on Europe, but also with chapters on Australia, the United States and Canada, it provides a comparative analysis of the implementation, functioning and impact of public service training and education from the nineteenth century to the present. In doing so, the book highlights two key influential factors: national political-administrative traditions and administrative tasks imposed by social, political, and economic change. It furthers our knowledge of the role of the state, both as an employer and as the implementer of public policy, and demonstrates how historical analysis can be utilised to inform present debates about public service training, government reform and good governance. This book will appeal to practitioners, as well as all those interested in public administration and its history, governance, public management, bureaucracy, and civil service reform. Toon Kerkhoff is Assistant Professor of Public Administration at Leiden University, The Netherlands. His research interests include administrative and political history, corruption and integrity, public values and ethics, and public sector reform. Denis Moschopoulos is Professor at the Ionian University of Corfu in Greece, where he holds the chair of the institutional and administrative history of the Greek state. His publications concern the institutional development of the Greek state and the historical evolution of its public administration.